Prosthodontic rehabilitation after traumatic tooth and bone loss: A clinical report - EVREN, BUKET (MOSBY-ELSEVIER, 2006)
Traumatic injuries from motor vehicle accidents may cause anatomic deficiencies in soft and hard tissues. Successful treatment of patients with such deficiences may include preprosthetic surgery using osseointegrated implants to increase prosthesis retention and stability. This article describes the treatment of a motor vehicle accident victim whose anterior teeth and supporting tissues were lost.
Keywords: OSSEOINTEGRATED IMPLANTS; PATIENT